A Non-targeted Metabolomics Approach Unravels the VOCs Associated with the Tomato Immune Response against Pseudomonas syringae - López-Gresa, María Pilar; Lisón, Purificación; Campos, Laura; Rodrigo, Ismael; Rambla, José Luis; Granell, Antonio; Conejero, Vicente; Bellés, José María (Frontiers in Plant Science, 2017)
Volatile organic compounds (VOCs) emitted by plants are secondary metabolites that mediate the plant interaction with pathogens and herbivores. These compounds may perform direct defensive functions, i.e. acting as antioxidant, antibacterial or antifungal agents, or indirectly by signalling the activation of the plant’s defensive responses. Using a non-targeted GC-MS metabolomics approach, we identified the profile of the VOCs associated with the differential immune response of the Rio Grande tomato leaves infected with either virulent or avirulent strains of Pseudomonas syringae DC3000 pv. tomato. The VOC profile of the tomato leaves infected with avirulent bacteria is characterised by esters of (Z)-3-hexenol with acetic, propionic, isobutyric or butyric acids, and several hydroxylated monoterpenes, e.g., linalool, α-terpineol and 4-terpineol, which defines the profile of an immunised plant response. In contrast, the same tomato cultivar infected with the virulent bacteria strain produced a VOC profile characterised by monoterpenes and SA derivatives. Interestingly, the differential VOCs emission correlated statistically with the induction of the genes involved in their biosynthetic pathway. Our results extend plant defence system knowledge and suggest the possibility for generating plants engineered to over-produce these VOCs as a complementary strategy for resistance.